# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \sqrt {1-x^{2}-y^{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime }+\frac {y}{3} = \frac {\left (1-2 x \right ) y^{4}}{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y}+x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y^{2} = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+x^{2} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{x +y} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {5 x^{2}-x y+y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}2 t +3 x+\left (x+2\right ) x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{1-y}
\] |
✓ |
✓ |
|
\[
{}p^{\prime } = a p-b p^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2}+\frac {2}{x}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x f^{\prime }-f = \frac {{f^{\prime }}^{2} \left (1-{f^{\prime }}^{\lambda }\right )^{2}}{\lambda ^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 y+b y^{2} = c \,x^{4}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y+y^{2} = x^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}u^{\prime }+u^{2} = \frac {1}{x^{{4}/{5}}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }-y = x
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 1-x {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}f^{\prime } = \frac {1}{f}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -4 \sin \left (x -y\right )-4
\] |
✗ |
✓ |
|
\[
{}y^{\prime }+\sin \left (x -y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 4 A k \left (\frac {x}{A}\right )^{{3}/{4}}-3 k x
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime } y}{1+\frac {\sqrt {1+{y^{\prime }}^{2}}}{2}} = -x
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime } y}{1+\frac {\sqrt {1+{y^{\prime }}^{2}}}{2}} = -x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (1+\frac {a^{2} x}{\sqrt {a^{2} \left (x^{2}+1\right )}}\right )}{\sqrt {a^{2} \left (x^{2}+1\right )}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+x^{2}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y \left (x \sqrt {y}-1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y^{2}-x -x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = -\frac {1}{2}-\frac {\sqrt {1-12 w}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x^{2} \sin \left (\frac {y}{x}\right )^{2}+\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}v v^{\prime } = \frac {2 v^{2}}{r^{3}}+\frac {\lambda r}{3}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = \sec \left (x \right )^{4}
\] |
✗ |
✗ |
|
\[
{}\left (y-2 x y^{\prime }\right )^{2} = {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (1-y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}h^{2}+\frac {2 a h}{\sqrt {1+{h^{\prime }}^{2}}} = b^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{2 y \ln \left (y\right )+y-x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+{\mathrm e}^{-y} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y+3 x -2 y+6}{x y-3 x -2 y+6}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = b y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y^{2}
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x +y
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x +b y
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = b y
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = a x +b y^{2}
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = \frac {a x +b y^{2}}{r}
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = \frac {a x +b y^{2}}{r x}
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = \frac {a x +b y^{2}}{r \,x^{2}}
\] |
✓ |
✓ |
|
\[
{}c y^{\prime } = \frac {a x +b y^{2}}{y}
\] |
✓ |
✓ |
|
\[
{}a \sin \left (x \right ) y x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}f \left (x \right ) \sin \left (x \right ) y x y^{\prime } \pi = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right )+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right )+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )+\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )+\frac {y^{2}}{x}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = x +y+b y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\pi y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}f \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y \sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\pi y \sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \sin \left (x \right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{n} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{n} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = x
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = x +y
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = \frac {y^{2}}{x}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = \frac {y^{3}}{x}
\] |
✓ |
✓ |
|